Role of hyperhomocysteinemia in atherosclerosis: from bench to bedside - Wende Tian; Jianqing Ju; Baoyi Guan; Tongxin Wang; Jiqian Zhang; Luxia Song; Hao Xu (Annals of Medicine)
Background Atherosclerosis is a leading cause of global mortality, driven by complex interactions between genetic, metabolic, and environmental factors. Among these, hyperhomocysteinemia (HHcy) has emerged as a significant and modifiable risk factor, contributing to endothelial dysfunction, oxidative stress, and vascular inflammation. Despite increasing recognition of its role in atherogenesis, the precise mechanisms and clinical implications of HHcy remain incompletely understood, necessitating a comprehensive review to connect recent mechanistic insights with practical applications.Methods We analyzed the various mechanisms whereby HHcy accelerates the progression of atherosclerosis, and conducted a comprehensive review of publications in the fields of HHcy and atherosclerosis.Results HHcy promotes atherosclerosis through several mechanisms, including inflammation, oxidative stress, epigenetic modification, and lipoprotein metabolism alteration. Moreover, this discussion extends to current strategies for the prevention and clinical management of HHcy-induced atherosclerosis.Conclusion This review consolidates and elucidates the latest advancements and insights into the role of HHcy in atherosclerosis. The comprehensive narrative connects fundamental research with clinical applications. Contemporary studies highlight the complex interplay between HHcy and atherosclerosis, establishing HHcy as not only a contributing risk factor but also an accelerator of various atherogenic processes.